1983
DOI: 10.1530/acta.0.1040385
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of a dopaminergic drug (piribedil) on pituitary hormone release in normal men and women

Abstract: Six normal women, in the follicular phase of their menstrual cycle, and 6 normal men received orally 40, 60 and 100 mg doses of piribedil, a dopamine receptor agonist, or placebo. The effects of piribedil on anterior pituitary hormone release was evaluated. In normal women a dose-related decrease in Prl levels was observed, while in men the Prl decrement was not related to the dose employed. In women an increase in serum hGH occurred after administration of the lowest (40 mg) dose of piribedil. In normal men, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
7
0

Year Published

1986
1986
2010
2010

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“…The intra-assay and interassay coefficients of variation ranged from 2.5 to 3.9% and from 5.8 to 8.5%, respectively. Plasma concentra tions of estradiol, progesterone and testosterone were measured by RIA, as previously described [13,14]. All samples from a given study were measured in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…The intra-assay and interassay coefficients of variation ranged from 2.5 to 3.9% and from 5.8 to 8.5%, respectively. Plasma concentra tions of estradiol, progesterone and testosterone were measured by RIA, as previously described [13,14]. All samples from a given study were measured in the same assay.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the dopaminergic activity of Piribedil, 10 the lack of PRL inhibition may be due to the low dose used. 14 The GH response is more complex. In normal subjects, there is a different sex response; in women the response seems to be related to the administered dose 14 ; that is, high doses of Piribedil give a GH release less than that obtained by low dose of the drug; there an inverse relationship between stimulus and response.…”
Section: Resultsmentioning
confidence: 99%
“…14 The GH response is more complex. In normal subjects, there is a different sex response; in women the response seems to be related to the administered dose 14 ; that is, high doses of Piribedil give a GH release less than that obtained by low dose of the drug; there an inverse relationship between stimulus and response. In our study we have shown a greater GH response in normal subjects than in migraine patients, as if in the normals the drug dose was lower.…”
Section: Resultsmentioning
confidence: 99%
“…Plasma concentrations of estradiol, progesterone, testosterone and cortisol were measured using RIA as previously described (7,8). All samples from a given study were measured in the same assay for each hormone.…”
Section: Methodsmentioning
confidence: 99%
“…In the same subjects, peripherally injected CRH (100 \g=m\g)significantly inhibited the GH response to GHRH (GH peaks 8.1 \m=+-\0.6\g=m\g/l in men, p<0.005 and 9.9\m=+-\0.7\g=m\g/l in women, p<0.005). In an attempt to clarify the mechanism of the CRH action, we have studied the effect of enhanced cholinergic tone induced by pyridostigmine on the CRH inhibition of the GH response to GHRH in a group of six normal men and six normal women.…”
mentioning
confidence: 87%